2015
DOI: 10.3389/fgene.2015.00005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of autozygosity in Nellore cows (Bos indicus) through high-density SNP genotypes

Abstract: The use of relatively low numbers of sires in cattle breeding programs, particularly on those for carcass and weight traits in Nellore beef cattle (Bos indicus) in Brazil, has always raised concerns about inbreeding, which affects conservation of genetic resources and sustainability of this breed. Here, we investigated the distribution of autozygosity levels based on runs of homozygosity (ROH) in a sample of 1,278 Nellore cows, genotyped for over 777,000 SNPs. We found ROH segments larger than 10 Mb in over 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 40 publications
(55 reference statements)
5
63
1
2
Order By: Relevance
“…The poor correlation reported in our study between F GRM and F ROH was according to other studies Zhang et al, 2015). Zavarez et al (2015) in a study on autozygosity using high-density SNPs, showed that the correlation between F GRM and F ROH decreased from 0.74 per ROH >0.5 Mb to 0.41 per ROH >16 Mb, probably due to the properties of the G matrix which is based on individual loci, whereas F ROH is based on chromosomal segments. A higher correlation between F MOL i and F ROH were reported by Gómez-Romano et al (2014) in Austrian Brown Swiss cattle (0.76) and Rodríguez-Ramilo et al (2015) in Spanish Holstein breed (0.88).…”
Section: Resultscontrasting
confidence: 62%
“…The poor correlation reported in our study between F GRM and F ROH was according to other studies Zhang et al, 2015). Zavarez et al (2015) in a study on autozygosity using high-density SNPs, showed that the correlation between F GRM and F ROH decreased from 0.74 per ROH >0.5 Mb to 0.41 per ROH >16 Mb, probably due to the properties of the G matrix which is based on individual loci, whereas F ROH is based on chromosomal segments. A higher correlation between F MOL i and F ROH were reported by Gómez-Romano et al (2014) in Austrian Brown Swiss cattle (0.76) and Rodríguez-Ramilo et al (2015) in Spanish Holstein breed (0.88).…”
Section: Resultscontrasting
confidence: 62%
“…; Zavarez et al . ), given their high correlation with autozygosity (r ≈ 0.7) (McQuillan et al . ) and, consequently, the high accuracy with which autozygosity is detected (Keller et al .…”
Section: Introductionmentioning
confidence: 99%
“…The genomic-based inbreeding method correlated moderately or poorly with pedigree 319 data, showing values lower than 0.39 (Figure7 to 9). Similary weak or no correlation was 320 reported for cattle [24,45,47], whereas a moderate to strong positive correlation was 321 described by some authors [15,40,48,59]. An increase in the correlation between genomic-322 and pedigree-based inbreeding as the pedigree depth increases is expected [24].…”
Section: Inbreeding Coefficients Correlations 312mentioning
confidence: 63%